Eficiencia técnica en los sistemas de producción ganadera bovina del noreste de la provincia de La Pampa (Ciencia Veterinaria, 2017)
Livestock farms in the northeast of La Pampa were classified according to their productivity by using a technical efficiency index.This objective was achieved, calculating in the first place, the function of production using a lineal regression model with explanatory variables, such as acres of green onion, acres of pasture, total number of animals and costs of supplementation; then the production frontier was calculated.The technical efficiency index (IET) relates the observed value with the potential value, according to the following equation IET =VO/VF = y/yf. Farms were classified into high, medium and low efficiency, according the IET. Linking farms by its size (area) and efficiency, the largest number of the same, are observed (16 above 56). Finally, with the explanatory variables by univariate ANOVA, farms were distinguished and concluded that the cost of supplementation was the only explanatory of efficiency variable.
Keywords: beef farms; efficiency; La Pampa